In vitro equivalence testing of immediate-release tablets using a model-independent mathematical approach - Quizon, Paul Marvin T. 1983-
At present, bioequivalence testing is the generally accepted method of demonstrating therapeutic equivalence and drug product interchangeability. However, the disadvantages associated with in vivo studies brought about the development of in vitro equivalence tests and biowaivers based on the Biopharmaceutics Classification System. This study was conducted to determine the in vitro equivalency of selected commercially-available generic amlodipine besylate immediate-release 10-mg tablets with the innovator using similarity factor (f2) estimate. The potency and purity of the tablets were also determined using the HPLC assay from USP 34/NF 29. Results showed that all tested products conformed to the specifications for amlodipine content and impurity level. Evaluation of the dissolution profiles showed that majority of the generic versions were considered to be equivalent in vitro to the innovator based on the WHO criteria of 50 to 100 for dissolution profile similarity. However, using the narrower acceptance range of 80 to 100 set for the study, all generic versions were not considered to be equivalent in vitro. Based on the results of the study, in vitro equivalence testing using the model-independent mathematical approach can demonstrate the possible equivalency for amlopidine besylate, a highly soluble and highly permeable drug, formulated as immediate-release 10-mg tablet.